Chapter 2: 'Celtic Spells and Counterspells' from Book: Understanding Celtic Religion: Revisiting the Pagan Past - Jacqueline Borsje (New Approaches to Celtic Religion and Mythology, 2015)
This is a chapter from Understanding Celtic Religion: Revisiting the Pagan Past, edited by Katja Ritari and Alexandra Bergholm. Although it has long been acknowledged that the early Irish literary corpus preserves both pre-Christian and Christian elements, the challenges involved in the understanding of these different strata have not been subjected to critical examination. This volume draws attention to the importance of reconsidering the relationship between religion and mythology, as well as the concept of 'Celtic religion' itself. When scholars are attempting to construct the so-called 'Celtic' belief system, what counts as 'religion'? Or, when labelling something as 'religion' as opposed to 'mythology', what do these entities entail? This volume is the first interdisciplinary collection of articles which critically reevaluates the methodological challenges of the study of 'Celtic religion'; the authors are eminent scholars in the field of Celtic Studies representing the disciplines of theology, literary studies, history, law and archaeology, and the book represents a significant contribution to the present scholarly debate concerning the pre-Christian elements in early medieval source materials.